A magyar keresztény terminológia bizánci rítusú szláv elemei - Zoltán András; Золтан Андраш; Zoltan Andras (Magyar Nyelvtudományi Társaság, 2020)
A magyar köznyelvi szókincs idegen eredetű elemei közül a legnagyobb tételt szláv jövevényszavaink teszik ki (Vermes 1941, Papp 1967: 521, vö. Zoltán 2017a: 1), természetes tehát, hogy a szláv eredetű szavak keresztény terminológiánkban is számosak és fontosak. Elég, ha néhány alapvető terminusra utalunk: kereszt, keresztel, keresztyén (ebből később a kereszt beleértésével keresztény); apáca, apát, barát ’szerzetes’, pap; pokol; szent, szentel; szerda, csütörtök, péntek, szombat; zarándok, vecsernye, zsolozsma. Ide tartozik néhány ma már főleg csak biblikus összefüggésben használt szó és szólás is: hálát ad, malaszt, nyoszolya, parázna, szövétnek.

Abstract. The 10th-century Byzantine conversion of Hungarians was carried out through Slavic mediation, as there were many Slavic-Hungarian bilinguals among the Hungarians settled in the midst of Slavic population, and Slavic-Greek bilingual missionaries were easy to find in the Balkan provinces of the Byzantine Empire (e.g. in Macedonia). Most of the early Slavic borrowings to Hungarian came from the Slavic substrate of the Carpathian Basin (Pannonian Slavic), and this is also true of Christian terminology. Due to the high degree of similarity between 10th-century Slavic dialects, it is difficult to separate terms locally borrowed from Pannonian Slavs from those introduced by the Byzantine missionaries speaking Slavic in Hungary. However, there are some words and expressions of Balkans origin (hálát ad ‘give thanks’, karácsony ‘Christmas’, pitvar ‘porch’, formerly ‘limbo, edge of Hell’, etc.) that could hardly have been found in Pannonian Slavic; these were most probably brought by the Byzantine missionaries and spread among the Hungarians.
Slavic elements of Byzantine rite in the Hungarian Christian terminology
https://epa.oszk.hu/00000/00032/00087/pdf/EPA00032_magyar_nyelv_2020_3.pdf
Keywords: etimológia; szláv jövevényszavak; bizánci térítés